THE DYNAMIC OF LANDSCAPE CHANGE AT COAST AREA, IN LABAKKANG SUBDISTRICT, PANGKEP REGENCY, SOUTH SULAWESI - andi GUsti Tantu; S Soemarno; Nuddin Harahab; Ahmad Mustafa (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Development is a changing process to improve human standard of life that strongly related to the activities of natural resource utilization. It is frequently found that these activities change the ecosystems and their resources. Eventually, these changes will give serious impacts to the environments. The most distinct environmental problems are caused by resident migration to the coastal areas, coastal developments, and land limitation. Coastal reclamation is an example of human effort to respond to the land limitation in the coastal areas as observed in coastal areas of Labakkang Subdistrict. Reclamation activity is doing along the coast of Pundata Baji Village, whereas, in other villages, cutting off of mangrove areas as an alternative land expansion is increasingly practiced by the local communities. This Research was aimed to observe the landscape change from 1980 to 2010 at coast area in Labakkang Subdistrict. Each review considers Landsat Image Map (acquired in 1980); Landsat Image Map (acquired in 1990); Landsat Image Map-7 Enhanced Thematic Mapper Plus (ETM+) (acquired in 2000); Spot Image 4 (acquired in 2005); and Spot 4 LAPAN (acquired in 2010). Result of research indicates that at coast area of Labakkang Subdistrict in 1980, there are 248.3 ha of mangrove vegetation, 2,756.63 ha inundation, and 4,157.0 ha open land. In 1990, there are 234.2 ha mangrove vegetation, 2,251.63 ha embankment, 933.2 ha rice field, and 582.0 ha open land. In 2000, there are 218.3 ha mangrove vegetation, 2,848.1 ha embankment, and 3,579.2 ha rice field. In 2005, it has 121.4 ha mangrove vegetation, 3,762.6 ha embankment, and 2,306.2 ha rice field. In 2010, it is found 48.9 ha mangrove vegetation, 5,029.35 ha embankment, and 749.98 ha rice field.